A clinical study of risk factors of acute pancreatitis in a tertiary care centre in north India - Jha, Pawan Kumar; Chandran, Rajnish; Jaiswal, Pradeep; Seema, Kumari (International Surgery Journal, 2017)
Background: According to Atlanta Symposium, acute pancreatitis (AP) was defined as an acute inflammatory process of the pancreas that may also involve peri-pancreatic tissues and/or remote organ systems. The objective of this study was to know the risk factors of acute pancreatitis in patients admitted in a tertiary care centre in north India Methods: A prospective study was performed with admitted cases of patients with acute pancreatitis over 2 years period. Total 104 patients were selected for study. All data concerning aetiology were recorded and analysed in all patients forming study groups. Results: Among 104 patients with acute pancreatitis 68 (65%) were females and 36 (35%) were males. Mean age of our study group was 40.9 years and maximum incidence was seen in 36-45 years. Most common cause was biliary pancreatitis (63%) followed by alcohol (27%), idiopathic (6%), trauma (3%), infections (1%). In females, most common aetiology was gall stone (88%), in males most commonly by alcohol (78%). As per Atlanta classification 81 patients (77.8%) had acute mild pancreatitis and 23 patients (22.2%) had acute severe pancreatitis. Majority females (66.7%) were admitted in mild acute pancreatitis. The mean age of patients in mild acute pancreatitis was 39.6 years and in severe group was 45.4 years. Gall stone were the leading cause in both mild and severe acute pancreatitis. Conclusions: Females were more commonly affected than men by acute pancreatitis. The most common aetiology was gall stone followed by alcohol which was leading cause in the males.